Enhanced thermoelectric performance via the solid solution formation: The case of pseudobinary alloy (Cu2Te)(Ga2Te3)3 upon Sb substitution for Cu. (5th February 2017) - Cui, Jiaolin; Liu, Xianglian; Du, Zhengliang; Chao, Yimin
Abstract: In this work we have observed the beneficial effect from the solid solution formation on the thermoelectric performance of (Cu2(1 − x ) Sb2 x Te)(Ga2 Te3 )3 upon Sb substitution for Cu. This substitution allows the different occupations of Sb in the crystal lattice, i.e. Sb at Cu sites with x ≤ 0.05 and at Ga sides with x ≥ 0.05, which has resulted in the Pisarenko relation does not exactly capture the measured Seebeck coefficient under assumed effective masses m *. The reduction of the lattice thermal conductivity ( κ L ) has been quantified within the temperature range from room temperature to 723 K. Over the entire composition range, the κ L value is reduced by 33% and 25% at temperature 723 K and 580 K, respectively. This observation is in a good agreement with the theoretical calculation based on the Callaway model used in the solid solutions. Along with the increasing of the mobility and electrical conductivity, the thermoelectric performance has been improved with the highest ZT value of 0.58 at 723 K, which is about double the value of intrinsic (Cu2 Te)(Ga2 Te3 )3 . Graphical abstract: Highlights: The reduction of the lattice thermal conductivity ( κ L ) has been quantified in Sb-incorporated (Cu2 Te)(Ga2 Te3 )3 alloy. A preference of Sb 3 + at Cu + site with x ≤ 0.05 and at Ga 3 + sides with x ≥ 0.05 has been determined. A remarkable improvement in TE performance has been achieved through solid solution formation.